Pemecahan Masalah Matematis Ditinjau dari Analisis Kesalahan Menggunakan Newman Procedure - Ponoharjo ponoharjo; Wikan Budi Utami; Fikri Aulia (Universitas Pancasakti Tegal, 2019)
This study aims to describe the errors of students in solving mathematical problem solving based on the newman procedure. This type of research is qualitative research. Based on the results of data analysis, the following conclusions are obtained: the location of the error (1) reading the question that is understanding the context of the sentence but cannot write the meaning correctly. (2) understanding the problem includes not writing what is known, writing what is known is not in accordance with the question request, not writing what is asked in the problem. (3) the transformation of the problem that there is a mistake in writing the method and not writing the method to be used. (4) process skills, namely concept errors and not writing down the calculation process. (5) writing the final answer that is not writing the final answer and conclusion in accordance with the context of the problem.